Implementasi K-Nearest Neighbor Untuk Klasifikasi Citra Wayang Beber Khas Pacitan - Purnamasari, Pricylia Oka Diah Ayu; Yama Hendra, R. Oktav; Wijaya, Indra (Algoritme Jurnal Mahasiswa Teknik Informatika, 2024)
The fading admirartion for the culture of one’s own country means that today’s generation is unaware of the art of wayang beber, wayang beber is the oldest wayang in Indonesia. Wayang beber flourished during the existence of the majapahit kingdom. Preserving wayang beber, which is now never played again, is the aim of the research, targeting the younger generation so that they get to know the charactters and storylines in wayang beber. The samples used in classifying wayang images to recognize wayang characters are three: Prabu Brawijaya, Dewi Sekartaji, and Joko Kembang Kuning. The method used in this research is Hue Saturation Value (HSV) for image extraction and the matlab application for processing digital image programs. From the research that has been carried out, accuracy results are up to 87%.